Strategi Manajemen Kelas Guru dalam Mewujudkan Pembelajaran Joyful Learning di Sekolah Dasar - Tita Putri Fadhilah; Sri Marmoah; Sukarno Sukarno (Didaktika Dwija Indria, 2026)
This study aims to examine teachers' classroom management strategies in realizing joyful learning in elementary schools. A qualitative approach was used with teachers and 23 fourth-grade elementary school students as subjects. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles and Huberman. The results showed that teachers implemented classroom management strategies through three integrated stages, namely a) planning, including the preparation of learning modules based on student needs, collaborative class agreements, varied methods and media, and light assessments, b) implementation, including managing the physical environment, enforcing rules with positive language, warm interactions, collaborative activities, utilizing digital media, and linking materials to real life, and c) evaluation, including continuous reflection, assessing the effectiveness of methods and media, identifying student needs, and designing solutions. This strategy actualizes the principles of joyful learning including enjoyable, student-centered, and collaboration and received positive responses from students in the form of a sense of comfort, enthusiasm, courage to participate, learning independence, and the ability to relate materials to everyday life. Obstacles encountered included time management, over-enthusiasm, differences in student abilities, group dynamics, and media limitations, which were overcome through adaptive solutions based on continuous reflection.